Exclusive Breastfeeding Practice and Its Associated Factors among Mothers of Infants Less Than Six Months of Age in Debre Tabor Town, Northwest Ethiopia: A Cross-Sectional Study - Getachew Arage; Haileyesus Gedamu (Advances in Public Health)
Background. Exclusive breastfeeding for the first six months of life is recommended by the World Health Organization and United Nations Children’s Fund. However, the prevalence of exclusive breastfeeding is very low in many developing countries including Ethiopia. Objectives. The study was aimed at assessing the prevalence of exclusive breastfeeding practice and its associated factors among infants aged six months in Debre Tabor town. Methods. Community based cross-sectional study was conducted. Simple random sampling technique was employed in the selection of participants. Data were collected using pretested and structured questionnaire through face-to-face interview. Odds ratios with their 95% CI were computed and variables having p value less than 0.05 in the multivariable logistic regression were considered as significantly associated with the dependent variable. Result. Of 470 mother-infant pair’s samples, 453 were included in the final analysis. The overall age appropriate rate of EBF practice was found to be 70.8%. Having an infant aged 2-3 months [AOR = 2.3 (95% CI: 1.12, 6.42)], giving birth in the health facility [AOR = 3.8 (95% CI: 2.18, 7.32)], being a house wife in occupation [AOR = 2.4 (95% CI (1.22, 6.92)], receiving counseling/advice on infant feeding [AOR = 2.1 (95% CI: 1.61, 5.41)], and colostrums feeding [AOR = 1.5 (95% CI: 1.28, 7.98)] were found to be significantly associated with EBF practice. Conclusion and Recommendations. A small proportion of infants are exclusively breastfed during the first 6 months. Promoting institutional delivery, revising the leave after birth, advice and counseling pregnant mothers about EBF, and enabling every mother to encourage colostrum feeding were recommended in order to increase the proportion of women practicing exclusive breastfeeding.